Narasi Ramah Lingkungan Sebagai Instrumen Persuasi Entitas Bisnis - Asep Kurnia Saputra; Darwadi Darwadi; Mulharnetti Syas (Universitas Palangka Raya, 2026)
This article examines how business entities construct eco-friendly narratives as strategic persuasive instruments in sustainable product advertising, operating through discursive and ideological mechanisms deliberately managed by corporations. Drawing on Norman Fairclough's Critical Discourse Analysis (CDA) framework, which dissects discourse across three analytical dimensions such as text, discursive practice, and social practice, as a lens to expose corporate ideology concealed beneath sustainability claims, this study analyses four eco-friendly product advertisements from international and domestic brands published between 2020 and 2026. Findings reveal that eco-friendly advertising narratives are constructed through three dominant discursive strategies: 1. Naturalization of consumer identity as a morally responsible environmental subject. 2. Reframing of consumption as a form of activism. 3. Linguistic greenwashing that conceals the contradictions of green capitalism behind vague sustainability lexicons. The study argues that business entities actively manage eco-friendly narratives not merely as informative messages, but as ideological apparatuses that strategically discipline consumer subjectivity, reproduce corporate hegemony, and legitimize green capitalism practices within ecological discourse. Implications for environmental communication studies, advertising regulation, and consumer critical literacy are discussed in the concluding section.